Analytical validation and establishment of reference intervals for a 'high-sensitivity' cardiac troponin-T assay in horses. Issue 1 (December 2016) - Shields, E.; Seiden-Long, I.; Massie, S.; Passante, S.; Leguillette, R.
Abstract Background Cardiac troponin-I assays have been validated in horses.'High-sensitivity' cardiac troponin assays are now the standard in human cardiology.Objective: Appropriately validate the'high-sensitivity' cardiac Troponin-T (hscTnT) assay for clinical use in horses, establish reference intervals, determine the biological variation, and demonstrate assay utility in selected clinical cases.Methods : Analytical validation of the Roche hscTnT assay included within- and between-run precision, linear dose response, limit of quantitation (LoQ), stability, and comparison with cTn-I (iSTAT). Reference intervals and biological variation were determined using adult, healthy, Non-Competition Horses (N = 125) and Racing-Thoroughbreds (N = 178). HscTnT levels were measured in two horses with cardiac pathology. Results The hscTnT demonstrates acceptable within-run (L1 = 6.5 ng/L, CV 14.9 %, L2 = 10.1 ng/L, CV 8.7 %, L3 = 15.3 ng/L, CV 5.4 %) and between-run precision (L1 = 12.2 ng/L, CV 8.4 %, L2 = 57.0 ng/L, CV 8.4 %, L3 = 256.0 ng/L, CV 9.0 %). The assay was linear from 3 to 391 ng/L. The LoQ was validated at 3 ng/L. Samples demonstrated insignificant decay over freeze-thaw cycle. Comparison with cTnI assay showed excellent correlation (range: 8.0–3535.0 ng/L, R2 = 0.9996). Reference intervals: The upper 95th and 99th percentile of the hscTnT population distribution were 6.8 and 16.2 ng/L in Non-Competition Horses, and 14.0 and 23.2 ng/L in Racing-Thoroughbreds. Between-breed, diurnal effect, and between-day variation was below LoQ. Two clinical cases with presumed cardiac pathology had hscTnT levels of 220.9 ng/L and 5723.0 ng/L. Conclusions This benchmark study is the first to comply with CLSI guidelines, thus further establishing the performance characteristics of the hscTnT assay, and reference intervals in healthy horses. Two clinical cases demonstrated further the clinical utility of the assay.